Cover Picture: Activation and Spillover of Hydrogen on Sub‐1 nm Palladium Nanoclusters Confined within Sodalite Zeolite for the Semi‐Hydrogenation of Alkynes (Angew. Chem. Int. Ed. 23/2019). Issue 23 (16th May 2019) - Wang, Shuai; Zhao, Zhi‐Jian; Chang, Xin; Zhao, Jiubing; Tian, Hao; Yang, Chengsheng; Li, Mingrun; Fu, Qiang; Mu, Rentao; Gong, Jinlong
Abstract : Hydrogen activation and spillover … renders the semi‐hydrogenation of acetylene over sub‐1 nm Pd nanoclusters confined within sodalite (SOD) zeolite (Pd@SOD) remarkably selective. In their Communication on page 7668 ff., R. Mu, J. Gong, and co‐workers show that H2 is dissociated on the Pd nanoclusters inside SOD to form hydrogen species that spill over the SOD surface. The utilization of the small‐pore zeolite SOD was crucial as it only allows H2 diffusion into the channels and thus prevents over‐hydrogenation to ethane.